Working Group Reports From ITiCSE on Innovation and Technology in Computer Science Education 2002
DOI: 10.1145/960568.782998
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of visualization and engagement in computer science education

Abstract: Visualization technology can be used to graphically illustrate various concepts in computer science. We argue that such technology, no matter how well it is designed, is of little educational value unless it engages learners in an active learning activity. Drawing on a review of experimental studies of visualization effectiveness, we motivate this position against the backdrop of current attitudes and best practices with respect to visualization use. We suggest a new taxonomy of learner engagement with visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(112 citation statements)
references
References 39 publications
2
102
0
5
Order By: Relevance
“…Contextual methods were evaluated in a few studies, mostly involving computer programming indicated mixed results. Two studies reported that creating animations helped students better understand concepts taught (Smith & Escott, 2004;Stasko, 1997), while another reported no statistically significant improvement when animations were used as teaching tools (Naps, et al, 2002). In another study, computer game use was favorable due to feedback providing instant gratification (Natvig & Line, 2004).…”
Section: Instructional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contextual methods were evaluated in a few studies, mostly involving computer programming indicated mixed results. Two studies reported that creating animations helped students better understand concepts taught (Smith & Escott, 2004;Stasko, 1997), while another reported no statistically significant improvement when animations were used as teaching tools (Naps, et al, 2002). In another study, computer game use was favorable due to feedback providing instant gratification (Natvig & Line, 2004).…”
Section: Instructional Methodsmentioning
confidence: 99%
“…Kolb, 1985;Wulf, 2005). Constructivist theory was chosen as the framework for this study due to its humanistic, engaging, and reflective tenets that are not commonplace in IT-related courses as they tend to attract students who are more oriented to traditional methods of instruction used in learning computer programming (Kolb, 1985;Lui, Kwan, Poon, & Cheung, 2004;Naps et al, 2002;Natvig & Line, 2004;Wulf, 2005).…”
Section: Learning Environmentmentioning
confidence: 99%
“…The use of Algorithm Visualization (AV) has soared in popularity over the years [17,22]. However, rather than reviewing all simulators and educational tools available to Computer Science, our aim is to focus on those most relevant to the topic of this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Studies [1]- [2] have shown that in order to improve student learning in CS, traditional pedagogical approaches are not enough to transfer critical knowledge to students. More interactive teaching and learning strategies are necessary to make learning more productive.…”
Section: Introductionmentioning
confidence: 99%